Factors that Influence Interest Repurchase Tourist Visitors - Dian Wahyuningsih (Almana : Jurnal Manajemen dan Bisnis, 2021)
The shift in public opinion regarding tourism needs is supported by the acceleration of information technology which has an impact on the rapid development of the tourism industry. Bandung is one of the tourist destinations that offer a variety of the latest destinations, including Kampoeng Tulip Ciwastra Bandung. The purpose of this study is to determine and analyze visitors to Kampoeng Tulip Ciwastra Bandung. This study uses descriptive and verificative methods with a quantitative approach. Sampling was done by non-probability sampling method, namely incidental sampling with a total of 100 respondents. The data analysis method used is path analysis. The results showed that partially experiential marketing affected repurchase interest by 34.4% and service quality affected repurchase interest by 29.1%. The simultaneous influence between experiential marketing and service quality on repurchase interest is 63.5%.